Raman spectra and structural peculiarities of TeO2–TeO3 mixed oxides. (5th November 2018) - Smirnov, M; Kuznetsov, V; Roginskii, E; Cornette, J; Dutreilh-Colas, M; Noguera, O; Masson, O; Thomas, P
Abstract: Raman spectra of the mixed crystalline oxides of the (1 − x )TeO2 + x TeO3 ( x = 0, ¼, ½, 1) series were recorded and simulated by using the DFT calculations. Good agreement between observed and calculated Raman spectra makes it possible to establish unambiguous assignment for all prominent Raman lines. This result gives an insight into relations between structural peculiarities and observed spectral features for the crystals promising as nonlinear optical materials. Highlights Several mixed TeO2 –TeO3 crystals were synthesized by solid-state chemistry DFT calculations well describe structures and phonon spectra of TeO2 –TeO3 oxides Raman lines can be assigned to internal vibrations of TeO4 and TeO6 polyhedrons Observed Raman bands can be used as fingerprints of different structural units